1983
DOI: 10.1161/01.str.14.5.791
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethanol in diluents of drugs that protect mice from hypoxia.

Abstract: SUMMARY This study evaluates the hypothesis that ethanol alone, or in diluents for drugs used to protect hypoxic mice, is responsible in part for an increased tolerance to hypoxia (4-5% oxygen). The change in hypoxic tolerance following i.v. or i.p. administration of ethanol, diazepam, nimodipine and various diluent components was measured. Diazepam (50 mg/kg i.v.) increased hypoxic tolerance to 700 ± 47% (n = 11) of saline control, its diluent increased hypoxic tolerance to 468 ± 60% (n = 10) of saline contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…22 Depressant agents are known to exert protective effects in hypoxic and ischemic situations by reducing the cerebral metabolic rate, and ethanol has been reported to prolong survival in hypoxic mice. 23 However, our results indicate that ethanol, unlike butanediol, does not prevent the development of edema secondary to embolization and are consistent with those of other studies that reported no beneficial effect of ethanol in various models of brain injury. Pretreatment with 47 mmol/kg ethanol, unlike pretreatment with butanediol, did not increase survival time in the Levine rat model, 24 and high doses of ethanol (87 mmol/kg) potentiated traumatic spinal cord and cerebral hemisphere damage in cats.…”
supporting
confidence: 91%
“…22 Depressant agents are known to exert protective effects in hypoxic and ischemic situations by reducing the cerebral metabolic rate, and ethanol has been reported to prolong survival in hypoxic mice. 23 However, our results indicate that ethanol, unlike butanediol, does not prevent the development of edema secondary to embolization and are consistent with those of other studies that reported no beneficial effect of ethanol in various models of brain injury. Pretreatment with 47 mmol/kg ethanol, unlike pretreatment with butanediol, did not increase survival time in the Levine rat model, 24 and high doses of ethanol (87 mmol/kg) potentiated traumatic spinal cord and cerebral hemisphere damage in cats.…”
supporting
confidence: 91%
“…Alcohols, specifically ethanol, have been reported to have cerebral protective actions. 9 However, ethanol did not significantly increase hypoxic survival time although the average survival time of the ethanol group tended to be higher than that of the saline controls. Butanediol-treated animals had a significantly longer hypoxic survival time compared with either the ethanol group or saline control group.…”
Section: Discussionmentioning
confidence: 77%